Mechanism and effects/impacts of money laundering in Bangladesh: preventive measures at Dhaka Bank’s AML-CFT department. - Momo, Sadia Islam (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.